Child sick care-related absence from work and the consequences on parents' income - Ayhan Adams; Katrin Golsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This study investigates the impact of child-related absence from work on the income of working mothers and fathers, addressing a significant research gap in sociology and labour economics. While previous research has established that gender and parenthood significantly influence income levels, the consequences of caring for a sick child-a common and unpredictable responsibility-remain inadequately explored. We utilise longitudinal data from the German Socio-Economic Panel Study (2010-2022) to examine how the accumulation of absence days due to child illness affects income levels and changes in income over four years among parents while controlling for various job and family-related characteristics. Our findings indicate that increased absenteeism related to child sickness adversely affects fathers' income, aligning with signalling theory, which suggests that absent workers may be perceived as less committed by employers. In contrast, mothers appear to experience less significant income impacts from similar absences, indicating that the stigma associated with absence days may be less pronounced. Additionally, we investigate the role of socio-economic status in these effects, finding that higher income positions do not amplify the negative signalling associated with child-related absenteeism for fathers. Meanwhile, we observed no association between mothers' income and child sickness-related absence when distinguishing between higher and lower income positions, potentially indicating prevailing gendered expectations in the workplace. The results underscore the need for further research into the socio-economic implications of caring for a sick child and employer perceptions to gain deeper insights into the dynamics of work-life balance and career consequences.
Keywords: 330; child sick care; income; gender; signalling theory